PENGARUH MOTIVASI PENGETAHUAN PERPAJAKAN, MOTIVASI KARIR, MOTIVASI KUALITAS, MOTIVASI SOSIAL, DAN MOTIVASI EKONOMI TERHADAP MINAT MAHASISWA MENGIKUTI PROGRAM BREVET PAJAK - Apri Ani Rahayu; Teguh Erawati; Anita Primastiwi (Universitas Muhammadiyah Makassar, 2021)
The tax brevet is an effort to pursue the world of taxation as the first step for students and enthusiasts in a career in taxation. The lack of knowledge about the importance of this tax brevet makes students' interest in participating in the tax brevet low. This makes researchers interested in researching the influence of motivation that can affect student interest in participating in tax brevet. This background is the basis for conducting research with the title